Answer:
one
Step-by-step explanation:
Answer:
x = 2+
Step-by-step explanation:
The function that relates the distance traveled d to the time t is
The function that relates the distance travelled d to the time t is d = f(t) = 140t.
Speed is a scalar quantity which measures the rate of change of the position of an object without measuring on the direction.
In other words, it can be defined as the ratio of distance covered by an object to the time taken by the object to cover the distance.
The train leaves the station at time t = 0.
Distance travelled by the train = 280 kilometers
Time taken to travel the distance = 2 hours
Speed = Distance / Time
= 280 / 2
= 140 kilometers/ hour.
Given that train travels at a constant speed.
So for any distance 'd' and the time taken to travel the distance 't',
d / t = 140
d = 140t
d = f(t) = 140t
Hence the distance travelled by the train can be related to the time taken by the function, d = f(t) = 140t
To learn more about Speed, click :
#SPJ5
Answer:
d = 140t
Step-by-step explanation:
Answer:
D
Step-by-step explanation:
The rate of 12 meters per second means that the constant of proportionality (k) or slope = 12.
That is m/s = 12.
The table that has a constant of proportionality that equals 12 is the table that represents the statement given.
The table in option D has a constant of proportionality of 12, since the ratio of m/s for all its given pair of values will give us 12 all through.
Answer:
I think your answer is B
Step-by-step explanation:
An expression is defined as a set of numbers, variables, and mathematical operations. The value of −b²−2bx²−x when the value of x=-2 is −b²−8b + 4.
In mathematics, an expression is defined as a set of numbers, variables, and mathematical operations formed according to rules dependent on the context.
The value of the expression −b²−2bx²−x will be,
−b² − 2bx² − x
= − b² − 2b(-2)² − (-2)
= − b² − 8b + 4
Hence, the value of −b²−2bx²−x when the value of x=-2 is −b²−8b + 4.
Learn more about Expression:
#SPJ2
Answer:
x<-7
Step-by-step explanation:
Use inverse operations to solve
4 - ( x + 2 ) < -3 ( x+ 4)
first distribute the (-) sign and the (-3)
4 -x -2 < -3x -12
simplify
2 -x < -3x -12
simplify again, with inverse operations
2 -x < -3x -12
+3x +3x
2 + 2x < -12
-2 -2
2x < -14
/2 /2
x<-7
in 4 - (x + 2) < -3(x + 4), x < -7
isolate the variable by dividing each side by factors that don't contain the variable.
Answer:
85
Step-by-step explanation: